Nonlinear effect of irradiance on photoheterotrophic activity and growth of the aerobic anoxygenic phototrophic bacterium Dinoroseobacter shibae. (7th December 2017) - Piwosz, Kasia; Kaftan, David; Dean, Jason; Šetlík, Jiří; Koblížek, Michal
Summary: Aerobic anoxygenic photosynthetic bacteria are an important component of marine microbial communities. They produce energy in light using bacteriochlorophyll a containing photosystems. This extra energy provides an advantage over purely heterotrophic bacteria. One of the most intensively studied AAP bacteria is Dinoroseobacter shibae, a member of the environmentally important Roseobacter clade. Light stimulates its growth and metabolism, but the effect of light intensity remains unclear. Here, we show that an increase in biomass along an irradiance gradient followed the exponential rise to the maximum curve, with saturation at about 300 µmol photons m −2 s −1, without any inhibition at light intensities up to 600 µmol photons m −2 s −1 . The cells adapted to higher irradiance by reducing pigmentation and increasing the electron transfer rate. This additional energy allowed D. shibae to redirect the metabolism of organic carbon sources such as glucose, leucine, glutamate, acetate and pyruvate toward anabolism, resulting in a twofold increase of their assimilation rates. We provide equations that can be feasibly incorporated into the existing model of D. shibae metabolism to further advance our understanding of the role of photoheterotrophy in the ocean .